The Use of Interactive Virtual BIM to Boost Virtual Tourism in Heritage Sites, Historic Jeddah - Ahmad Baik (ISPRS International Journal of Geo-Information, 2021)
Today, moving from a two-dimensional environment to a more advanced interactive three-dimensional (3D) environment in the industries of architecture, engineering, and construction has become one of the most significant topics of interest. This is due to several primary advantages that the 3D environment can offer. Building information modeling (BIM) can be used as a highly advanced system to present a desired reality in a 3D interactive environment accompanied with 3D reality captured data, such as the point cloud data. As such, these 3D environments can be employed for more advanced uses, such as virtual reality and augmented reality technologies (VR and AR). Recently, BIM has been employed in the context of heritage (known as HBIM, or Heritage Building Information Modeling) for different purposes, such as to provide as-built information with the ability to interact with the end user and uploading information (e.g., historical photographs, documents about materials, or any past restoration projects) into the BIM model. This research will focus on providing an interactive rich virtual 3D model for heritage management. This virtual environment can be employed in cultural tourism and used for the abovementioned purposes. The research project has been adopted in the case of the Zainal Historical House (Bayt Zainal) located in the Historic District of Jeddah, Saudi Arabia. This house is described as one of the significant historical buildings in the historic district. The key aim for selecting this case study is to bridge the gap in architectural knowledge regarding these heritage buildings and their hybrid structural systems (i.e., integration of steel or concrete with the traditional “Mangbi” stone technique).